Properties and food packaging applications of solvent casting-made starch-based films incorporated with essential oils: a review - Othman, Siti Hajar; Kahar, Nurul Syafiqah; Nordin, Norhazirah; Ahmad Shapi'i, Ruzanna (Wiley, 2023)
Biopolymer films particularly starch films are promising alternatives to non-biodegradable petroleum-based materials because they are cheap, available in abundance, and biodegradable. Nonetheless, the weak mechanical and barrier properties of the films restrict their usage. Other additives such as essential oils (EOs) incorporate into the films may enhance the restricted properties and add functionality to films. However, knowledge of the effects of EOs addition in starch films across food packaging applications is not fully elucidated. This paper provides an overview of the various types of EOs used in the production of starch films produced via the solvent casting method, the effects of EOs on the properties of starch films, and the application of the films for food packaging, particularly for fruits and meats. The films bring a high potential to extend the shelf life of food due to the antioxidant and antimicrobial properties of the EOs.